Water-based heavy anti-corrosion coating and preparation method thereof

By using a three -layer structure of water -based coating system, using water -based silicone acrylate hybrid epoxy resin and water -based FEVE resin and other materials to solve the problem of lack of heavy anticorrosive performance and slow drying speed in high corrosion environments. Achieve high -performance anticorrosive effects in the C5 environment.

CN119331510APending Publication Date: 2025-01-21SUZHOU DACHENG ENVIRONMENTAL PROTECTION NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411494101.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing water-based coatings have insufficient heavy corrosion resistance in high corrosion environments, slow drying and curing speeds, and are difficult to meet the special performance requirements of industrial coatings, such as acid and alkali resistance.

Method used

A three-component system of primer, a three-component system of mid-coat and a two-component system of topcoat are used. Water-based silicone acrylate hybrid epoxy resin and water-based FEVE resin are used in the primer, and basalt flakes are added to the mid-coat. and nano calcium carbonate, and leveling agent and water-based color paste are added to the topcoat.

Benefits of technology

It significantly improves the anti-corrosion performance and drying speed of water-based coatings, can be used in C5 environments, and meets special performance requirements such as acid and alkali resistance of industrial coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005100822780000061
    Figure BDA0005100822780000061
  • Figure BDA0005100822780000071
    Figure BDA0005100822780000071
  • Figure BDA0005100822780000081
    Figure BDA0005100822780000081
Patent Text Reader

Abstract

The invention relates to the field of anti-corrosion coatings, and particularly discloses a water-based heavy-duty anti-corrosion coating and a preparation method thereof. The water-based heavy anti-corrosion coating sequentially comprises a primer of a three-component system, a floating coat of the three-component system and a finishing coat of a two-component system, raw materials of the primer, the floating coat and the finishing coat comprise composite resin prepared from water-based organic silicon acrylate hybrid epoxy resin and water-based FEVE resin and a curing component containing nano calcium carbonate; the primer and the floating coat further comprise reinforcing powder containing slag powder and powdery sodium silicate. The water-based heavy anti-corrosion coating can be used for a water-based metal heavy anti-corrosion system in a marine environment and an industrial high-corrosion environment, the C5VH-level heavy anti-corrosion performance requirement can be met, and the requirements for environmental protection and low-carbon emission can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of anti-corrosion coatings, and more specifically, to a water-based heavy-duty anti-corrosion coating and a preparation method thereof. Background Art

[0002] As the country pays more and more attention to environmental protection, various environmental protection policies have been issued, which have a huge impact on the development of China's new materials industry. Among them, the ban on the use of high-VOCs solvent-based coatings and the promotion of low-VOCs coatings such as water-based coatings have become the focus. The "Catalogue of Toxic and Hazardous Raw Materials (Products) Substitutes Encouraged by the State (2016 Edition)" issued in 2016 proposed various types of water-based coatings to replace solvent-based coatings. Especially in the field of industrial coatings, such as building materials, high-speed rail, marine engineering and other industries, more emphasis is placed on the use of water-based coatings. Under the background of "carbon peak and carbon neutrality", the state's supervision of VOC emissions has become increasingly strict, and environmentally friendly anti-corrosion coatings have ushered in an opportunity for development.

[0003] Currently, the most widely used heavy-duty anti-corrosion paint for metals is solvent-based paint, which contains a large amount of volatile organic compounds (generally more than 60 parts), causing serious pollution to the environment. In addition, organic solvents need to be used as diluents and cleaning agents during the construction of solvent-based paints, and there are also flammable and explosive safety hazards during transportation and storage. Although the environmental performance of solvent-free heavy-duty anti-corrosion paints has been significantly improved, the construction performance often fails to meet the requirements due to excessive viscosity, resulting in problems with construction quality and anti-corrosion performance. In particular, for anti-corrosion maintenance projects that require on-site construction, since it is impossible to provide spraying and baking conditions similar to those equipped by the original factory, the coating can only be applied and cured on-site. In order to solve the construction operability problem of the paint, additional diluents have to be added, resulting in VOC emissions.

[0004] The emergence of water-based anti-corrosion coatings based on water-based resins provides a feasible technical means to solve the environmental pollution problem of anti-corrosion coatings. Compared with traditional solvent-based coatings, water-based anti-corrosion coatings completely or partially replace organic solvents with water, which has great advantages in controlling volatile organic compound (VOC) emissions. The VOC content of water-based coatings is generally much lower than that of solvent-based coatings, which can significantly reduce carbon emissions. Tap water can be used as a diluent and cleaning agent during construction, and there is no hidden danger of flammability and explosion during transportation and storage.

[0005] In view of the above-mentioned related technologies, the inventors found that the water-based coatings commonly used in the market currently have the following typical problems: 1) Slow drying and curing, especially in humid environments; 2) It is difficult to meet some special performance requirements for industrial coatings, such as acid and alkali resistance; 3) Water-based paint can only be used in C4 environment at most and cannot meet the requirements for use in C5 environment. For example, in the national chemical industry standard "HG / T5176-2017 Water-based anti-corrosion paint for steel structure", the highest requirement for water-based paint is C4H, and the neutral salt spray resistance time requirement is 720 hours. Summary of the invention

[0006] In order to improve the heavy-duty anti-corrosion performance of water-based coatings in highly corrosive environments, the present application provides a water-based heavy-duty anti-corrosion coating and a preparation method thereof.

[0007] In the first aspect, the present application provides a water-based heavy-duty anti-corrosion coating, which adopts the following technical solution: A water-based heavy-duty anticorrosive coating comprises, in sequence, a primer of a three-component system, a mid-coat of a three-component system, and a topcoat of a two-component system; the raw materials of the primer comprise a composite resin, a curing component, and a zinc-rich reinforcing powder in a mass ratio of 2:1:(2.5-3); the raw materials of the mid-coat comprise a composite resin, a curing component, and an active reinforcing powder in a mass ratio of 1:1:(0.8-1.2); the raw materials of the topcoat comprise a composite resin and a curing component in a mass ratio of 2:1; the raw materials of the composite resin in the primer, mid-coat, and topcoat all comprise water-based organosilicon acrylate hybrid epoxy resin and water-based FEVE resin; the raw materials of the curing component in the primer, mid-coat, and topcoat all comprise nano-calcium carbonate; the raw materials of the zinc-rich reinforcing powder and the active reinforcing powder all comprise powdered sodium silicate; and the active reinforcing powder comprises basalt flakes.

[0008] By adopting the above technical solution, the water-based silicone acrylate hybrid epoxy resin combines the performance advantages of silicone, acrylic acid and epoxy resin, and can form a coating with good density, weather resistance and adhesion with the metal base. Although the water-based FEVE resin has excellent weather resistance, salt spray resistance and acid and alkali resistance, as the main component of water-based fluorine-containing coatings, it has the disadvantages of high preparation cost, low cross-linking density after curing, and poor wettability to fillers, which will make the adhesion between the formed coating and the metal base poor.

[0009] Waterborne organosilicon propionate hybrid epoxy resin can make up for all the above defects of FEVE resin. By preparing a composite resin of hybrid resin and FEVE resin as the main matrix material of the coating, on the one hand, the primer, midcoat and topcoat of the coating can be made highly environmentally friendly, with VOC emissions and the content of harmful substances far lower than the requirements of relevant standards, and on the other hand, the adhesion between the coating and the metal substrate can be significantly enhanced, thereby enhancing the heavy-duty anti-corrosion performance of the coating.

[0010] In the zinc-rich reinforcing powder of the primer and the active reinforcing powder of the mid-coat, the ultrafine slag powder and the alkaline sodium silicate can undergo an alkali-activated active reaction. As an alkali activator, powdered sodium silicate can react with the acidic groups in the water-based resin, promote the cross-linking between the polymer chains in the coating, accelerate the curing process of the coating, and effectively cut off the channels formed by the volatilization of water after the water-based resin film is formed, forming a uniform and dense coating before the water completely evaporates, significantly improving the sealing effect of the water-based composite resin coating. While promoting curing, it can also speed up the drying speed of the coating. Designing powdered sodium silicate into the powder formula can also prevent it from affecting the stability of the emulsion component or the curing component in the liquid.

[0011] Nano calcium carbonate is added to the curing component of the present application, and the nano calcium carbonate can be filled into the microstructure of the coating, significantly improving the density of the coating, helping to reduce the pores and defects of the coating, thereby improving the heavy anti-corrosion performance of the coating. Hydrophilic nano calcium carbonate is easier to disperse in an aqueous system and can be pre-dispersed in the curing component, which helps to reduce agglomeration, improve the dispersion stability of primer, midcoat and topcoat raw materials, promote the coating curing reaction, and improve the curing efficiency of the coating.

[0012] Optionally, the raw materials of the zinc-rich reinforcing powder include 15-20 parts of slag powder, 5-8 parts of Powdered sodium silicate and 72-80 parts zinc powder.

[0013] By adopting the above technical solution, zinc powder is a chemically active pigment, the electrode potential of zinc is -0.7628V, and the electrode potential of iron is -0.409V. Therefore, zinc can act as a sacrificial anode on the surface of steel, protecting the steel and preventing the metal substrate from being corroded. At the same time, the corrosion products of zinc powder can fill the pores of the coating and seal the damaged parts of the coating.

[0014] The sacrificial anode protection mechanism and physical bonding between the zinc powder and the substrate significantly enhance the bonding strength between the coating and the metal substrate, thereby improving the heavy-duty anti-corrosion performance of the coating.

[0015] Optionally, the raw materials of the activity enhancing powder include, by weight, 20-30 parts of slag powder, 1.5-2.5 parts of powdered sodium silicate, 10-20 parts of steel slag powder, 10-15 parts of basalt flakes, and 25-32.5 parts of quartz powder.

[0016] By adopting the above technical solution, a multi-layer structure is formed by the composite resin system and basalt flakes in the middle coating, forming a parallel stacking barrier effect, forcing the corrosive medium to penetrate in a circuitous way, thereby effectively delaying the path and time for the corrosive medium to diffuse and invade the metal surface.

[0017] The hydrates produced by the inorganic ultrafine powder after alkali excitation and the joint filling and dense reaction of nano-calcium carbonate form an intermediate barrier layer that can effectively isolate the corrosive medium, greatly increasing the difficulty of the corrosive medium entering the coating. Even if the corrosive medium enters, its circuitous penetration path is increased, significantly prolonging the time it takes to reach the metal surface.

[0018] Optionally, 10-33.5 parts of quartz sand are also included.

[0019] Optionally, in parts by weight, the composite resin raw material of the primer includes 80-90 parts of water-based silicone acrylate hybrid epoxy resin and 10-20 parts of water-based FEVE resin; the curing components of the primer include 12-13.5 parts of curing agent, 0.1-0.4 parts of wetting agent, 0.3-0.5 parts of dispersant, 0.2-0.5 parts of defoaming agent, 0.6-1.0 parts of film-forming aid, 5-8 parts of nano calcium carbonate and 26.1-31.8 parts of water.

[0020] Optionally, in parts by weight, the composite resin raw material of the mid-coat includes 70-90 parts of water-based silicone acrylate hybrid epoxy resin and 10-30 parts of water-based FEVE resin; the curing component raw materials of the mid-coat include 10-15 parts of curing agent, 0.3-0.5 parts of wetting agent, 0.4-0.8 parts of dispersant, 0.3-0.6 parts of defoaming agent, 0.6-1.0 parts of film-forming aid, 0.3-0.6 parts of anti-settling agent, 0.3-0.6 parts of cellulose ether, 30-40 parts of nano calcium carbonate and 40.9-58.8 parts of water.

[0021] By adopting the above technical solution, anti-settling agent and cellulose ether are added to the middle coating, which can help prevent the pigment from settling, ensure the uniformity of the coating, and ensure the excellent performance of the coating.

[0022] Optionally, in parts by weight, the composite resin raw material of the topcoat includes 60-70 parts of water-based silicone acrylate hybrid epoxy resin and 30-40 parts of water-based FEVE resin; the raw materials of the curing component of the primer include 9-10.5 parts of curing agent, 0.2-0.4 parts of wetting agent, 0.2-0.4 parts of dispersant, 0.2-0.5 parts of defoaming agent, 0.5-0.8 parts of film-forming aid, 0.2-0.4 parts of leveling agent, 3-6 parts of water-based color paste, 5-8 parts of nano calcium carbonate and 23.4-31.7 parts of water.

[0023] By adopting the above technical solution, leveling agent and water-based color paste are added to the topcoat. The addition of leveling agent helps to improve the surface smoothness of the coating and enhance the appearance quality; while the addition of water-based color paste can provide good color stability and color retention, and enhance the weather resistance of the coating.

[0024] Optionally, the curing agent is a water-based non-ionic fatty amine curing agent.

[0025] In a second aspect, the present application provides a method for preparing a water-based heavy-duty anti-corrosion coating, using the following technical solution: An application of a water-based heavy-duty anti-corrosion coating comprises the following steps: The composite resin, curing component and zinc-rich reinforcing powder of the primer are prepared according to the raw material ratio, the three components are evenly mixed to obtain the primer, and the primer is rolled or sprayed on the metal surface, and the primer layer is obtained after drying and curing; The composite resin, curing component and active enhancement powder of the mid-coat are prepared according to the raw material ratio, the three components are evenly mixed to obtain the mid-coat, which is sprayed on the surface of the primer layer, and dried and cured to obtain the intermediate layer; The composite resin and curing component of the topcoat are prepared according to the raw material ratio, the two components are evenly mixed to obtain the topcoat, which is rolled or sprayed on the surface of the intermediate layer to form a surface layer, and is obtained after drying and curing.

[0026] By adopting the above technical solution, a coating is prepared with a three-layer structure of primer, mid-coat and topcoat, and the function of each layer is further optimized, thereby achieving heavy-duty anti-corrosion performance and service life of the entire coating system.

[0027] In summary, this application has the following beneficial effects: 1. This application uses a composite resin system made of water-based organic silicone acrylic hybrid epoxy resin and water-based FEVE resin to give the zinc-rich primer excellent adhesion to the metal surface. At the same time, through the active reaction of slag powder and powdered sodium silicate, the channel formed by water volatilization after the water-based composite resin film is effectively cut off, which significantly improves the sealing effect of the water-based composite resin coating and forms a high anti-corrosion ability on the metal surface together with zinc powder.

[0028] 2. As an intermediate layer, the mid-coat plays a connecting role in the overall anti-corrosion effect of the system. It forms a parallel superimposed barrier effect through a multi-layer flaky structure formed by the composite resin system and basalt flakes; the hydration products produced after the powdered sodium silicate is excited by alkali and the combined filling and densification effect of nano-calcium carbonate form a barrier layer in the middle layer that can effectively isolate the corrosive medium, effectively delaying the path and time of the corrosive medium to diffuse and invade the metal surface, greatly increasing the difficulty of the corrosive medium entering the coating.

[0029] 3. The coating of the present application achieves the ability to protect metals from rust in harsh corrosive environments through the cross-linking enhancement and sealing technology of water-based composite resins, the high adhesion and sealing technology of water-based zinc-rich primers to metal surfaces, the high barrier technology of intermediate coatings to corrosive media, and the high weather resistance and high color retention technology of protective surface layers. The anti-corrosion requirements reach C5VH level. DETAILED DESCRIPTION

[0030] The following examples further illustrate the present application in detail.

[0031] raw material Unless otherwise specified, the raw materials used in the preparation examples, embodiments and comparative examples in this application are all commercially available products, specifically: Silicone acrylate copolymer emulsion, selected from Intron Technologies, IRW; The free radical initiator is benzoyl peroxide, selected from West Asia Chemical, A65330; Bisphenol A epoxy resin, selected from Senqiang Environmental Technology, E-44; Water-based FEVE resin, selected from Daikin, ZEFFLE SE405; The curing agent is a water-based non-ionic fatty amine curing agent selected from Femtosecond Chemical, water-based polyurethane, FS-7; Wetting agent, selected from Evonik Digo, Twin4100; Dispersant, selected from BYK, BYK163; Defoaming agent, selected from BYKA, BYKA500; Film-forming aid, selected from Runtai Chemical, 23812; Anti-settling agent, selected from Zhonglian Federation, K-288; Cellulose ether, which is carboxymethyl cellulose, selected from Jianyang Xinghua, XH-666; Leveling agent, selected from BYK, BYK333; Water-based color paste, selected from AStrong, WVW107; Nano calcium carbonate, which is modified calcium carbonate, was selected from Hangzhou Jikang New Materials Co., Ltd., SS-CAC50; Slag powder, specific surface area ≥600㎡ / kg; Steel slag powder, specific surface area ≥ 600㎡ / kg; Basalt scales, selected from Anjie, 80-150 mesh; Quartz powder, 300 mesh; Quartz sand, 80-120 mesh.

[0032] Preparation method of waterborne organosilicon acrylate hybrid epoxy resin The water-based silicone acrylate hybrid epoxy resin comprises 50 g of silicone acrylate copolymer emulsion, 15 g of free radical initiator, 45 g of bisphenol A epoxy resin, 2 g of triethylamine and 150 g of p-hydroxyanisole.

[0033] The preparation method of water-based organosilicon acrylate hybrid epoxy resin comprises the following steps: In a nitrogen atmosphere, silicone acrylate copolymer emulsion, bisphenol A epoxy resin, free radical initiator and p-hydroxyanisole were stirred at 150°C and 350r / min for free radical polymerization for 3 hours, then cooled to 60°C, triethylamine was added dropwise for neutralization for 0.5h, and the product was obtained.

[0034] Primer Preparation Examples 1.1-1.4 Preparation Example 1.1 Primer, various raw materials and amounts are shown in Table 1.

[0035] Table 1 The preparation method of the above primer comprises the following steps: S1: mixing the waterborne silicone acrylate hybrid epoxy resin and the waterborne FEVE resin evenly to form a composite resin; S2: mixing the curing agent, wetting agent, dispersant, defoaming agent, film-forming aid, nano calcium carbonate and deionized water to form a curing component; S3: Evenly mix the slag powder, powdered sodium silicate and zinc powder to form a zinc-rich reinforced powder; S4: The composite resin, the curing component and the zinc-rich reinforcing powder are uniformly mixed in a mass ratio of 2:1:2.5 to obtain.

[0036] Preparation Example 1.2 The primer is different from the preparation example 1.1 in that the raw materials and amounts are as shown in Table 1, and in step S4, the composite resin, the curing component and the zinc-rich reinforcing filler are mixed in a mass ratio of 2:1:2.7, and the other steps are the same as the preparation example 1.1.

[0037] Preparation Example 1.3 The primer is different from the preparation example 1.1 in that the raw materials and amounts are as shown in Table 1, and in step S4, the composite resin, the curing component and the zinc-rich reinforcing filler are mixed in a mass ratio of 2:1:3, and the other steps are the same as those in the preparation example 1.1.

[0038] Preparation Example 1.4 The primer differs from Preparation Example 1.1 in that zinc powder is not added, and the zinc powder in the raw material is replaced by slag powder of equal mass, and the other steps are the same as Preparation Example 1.1.

[0039] Preparation Examples 2.1-2.5 of Midcoat Preparation Example 2.1 The raw materials and dosage of the midcoat are shown in Table 2.

[0040] Table 2 The method for preparing the above-mentioned mid-coat comprises the following steps: S1: mixing the waterborne silicone acrylate hybrid epoxy resin and the waterborne FEVE resin evenly to form a composite resin; S2: mixing a curing agent, a wetting agent, a dispersant, a defoaming agent, a film-forming aid, an anti-settling agent, a cellulose ether, nano-calcium carbonate and deionized water to form a curing component; S3: Evenly mix slag powder, steel slag powder, powdered sodium silicate, basalt flakes, quartz sand and quartz powder to form an active enhancement powder; S4: The composite resin, the curing component and the active enhancement powder are mixed evenly in a mass ratio of 1:1:0.8 to obtain.

[0041] Preparation Example 2.2 The difference between the middle coating and Preparation Example 2.1 is that the raw materials and their amounts are as shown in Table 2, and in step S4, the composite resin, the curing component and the active reinforcing filler are mixed in a mass ratio of 1:1:1, and the other steps are the same as Preparation Example 2.1.

[0042] Preparation Example 2.3 The difference between the mid-coat and Preparation Example 2.1 is that the raw materials and amounts are as shown in Table 2, and in step S4, the composite resin, the curing component and the active reinforcing filler are mixed in a mass ratio of 1:1:1.2, and the other steps are the same as Preparation Example 2.1.

[0043] Preparation Example 2.4 The difference between the mid-coat and Preparation Example 2.1 is that quartz sand is not added, and the other steps are the same as Preparation Example 2.1.

[0044] Preparation Example 2.5 The difference between the mid-coat and Preparation Example 2.1 is that basalt flakes are not added, and the basalt flakes in the raw materials are replaced with slag powder of equal mass, and the other steps are the same as Preparation Example 2.1.

[0045] Preparation of topcoat Examples 3.1-3.3 Preparation Example 3.1 Topcoat, various raw materials and amounts are shown in Table 3.

[0046] Table 3 The preparation method of the above-mentioned topcoat comprises the following steps: S1: mixing the waterborne silicone acrylate hybrid epoxy resin and the waterborne FEVE resin evenly to form a composite resin; S2: uniformly mixing a curing agent, a wetting agent, a dispersant, a defoaming agent, a film-forming aid, a leveling agent, a water-based color paste, nano calcium carbonate and deionized water to form a curing component; S3: The composite resin and the curing component are mixed evenly in a mass ratio of 2:1 to obtain.

[0047] Preparation Examples 3.2-3.3 Middle coating, the difference between Preparation Examples 3.2-3.3 and Preparation Example 3.1 is that the raw materials and amounts are shown in Table 3, and the other steps are the same as Preparation Example 3.1. Example

[0048] Example 1 A water-based heavy-duty anti-corrosion coating comprises a primer layer, an intermediate layer and a surface layer formed by a primer, a mid-coat and a topcoat, wherein sources of the primer, the mid-coat and the topcoat are shown in Table 4.

[0049] Table 4 Group Primer Mid coat Topcoat Example 1 Preparation Example 1.1 Preparation Example 2.1 Preparation Example 3.1 Example 2 Preparation Example 1.1 Preparation Example 2.2 Preparation Example 3.3 Example 3 Preparation Example 1.2 Preparation Example 2.3 Preparation Example 3.1 Example 4 Preparation Example 1.2 Preparation Example 2.1 Preparation Example 3.3 Example 5 Preparation Example 1.3 Preparation Example 2.2 Preparation Example 3.1 Example 6 Preparation Example 1.3 Preparation Example 2.3 Preparation Example 3.2 The method for preparing the above-mentioned water-based heavy-duty anti-corrosion coating comprises the following steps: S1: Roll or spray the primer on the metal surface, and obtain a primer layer with a thickness of 50 μm after drying and curing; S2: spray the midcoat on the surface of the primer layer, and after drying and curing, obtain an intermediate layer with a thickness of 100 μm; S3: Roll or spray the topcoat on the surface of the intermediate layer to form a surface layer with a thickness of 50 μm, and then dry and solidify it.

[0050] Embodiment 2-6 A water-based heavy-duty anti-corrosion coating. The difference between Examples 2-6 and Example 1 is that the sources of the primer, mid-coat and topcoat are shown in Table 4, and the other steps are the same as those in Example 1.

[0051] Example 7 A water-based heavy-duty anti-corrosion coating, which differs from Example 1 in that the primer is prepared by Preparation Example 1.4, and the other steps are the same as Example 1.

[0052] Example 8 A water-based heavy-duty anti-corrosion coating, which differs from Example 1 in that the mid-coat is prepared by Preparation Example 2.4, and the other steps are the same as Example 1.

[0053] Comparative Example Comparative Example 1 A water-based heavy-duty anti-corrosion coating, which differs from Example 1 in that no water-based silicone acrylate hybrid epoxy resin is added to the composite resins in the primer, mid-coat and topcoat, the water-based silicone acrylate hybrid epoxy resin in the raw material is replaced by an equal mass of water-based FEVE resin, and the other steps are the same as in Example 1.

[0054] Comparative Example 2 A water-based heavy-duty anti-corrosion coating, which differs from Example 1 in that no water-based FEVE resin is added to the composite resins in the primer, mid-coat and topcoat, the water-based FEVE resin in the raw material is replaced with an equal mass of water-based silicone acrylate hybrid epoxy resin, and the other steps are the same as Example 1.

[0055] Comparative Example 3 A water-based heavy-duty anti-corrosion coating, which differs from Example 1 in that no zinc-rich reinforcing powder is added to the primer, no active reinforcing powder is added to the midcoat, and other steps are the same as those of Example 1.

[0056] Comparative Example 4 A water-based heavy-duty anti-corrosion coating, which differs from Example 1 in that no nano calcium carbonate is added to the curing components in the primer, mid-coat and topcoat, and the other steps are the same as those in Example 1.

[0057] Comparative Example 5 A water-based heavy-duty anti-corrosion coating, which differs from Example 1 in that powdered sodium silicate is not added to the zinc-rich reinforcing powder of the primer and the active reinforcing powder of the mid-coat, and other steps are the same as those of Example 1.

[0058] Comparative Example 6 A water-based heavy-duty anti-corrosion coating, which differs from Example 1 in that the mid-coat is prepared by Preparation Example 2.5, and the other steps are the same as Example 1.

[0059] Performance testing Test Example 1 Environmental Test According to the standard of "Limits of Hazardous Substances in Industrial Protective Coatings" GB 30981-2020, the limit indicators of harmful substances in Examples 1-8 and Comparative Examples 1-6 were tested.

[0060] The results show that the water-based heavy-duty anti-corrosion coatings obtained in Examples 1-8 and Comparative Examples 1-6 are all below the environmental protection limit requirements, which indicates that the water-based heavy-duty anti-corrosion coating based on water-based composite resin in the present application has excellent environmental protection properties and will not cause excessive damage to the environment.

[0061] The specific test items and results are shown in Table 5.

[0062] Table 5 Test Example 2 Aging Resistance According to the standard of ISO 11507:2007, the coatings obtained in Examples 1-8 and Comparative Examples 1-6 were subjected to an anti-aging performance test by using an exposure cycle lasting one week (168 hours).

[0063] 1. The specific methods and standards are as follows: S1: 72h of UV and water exposure, conditions are as follows: 4h UV irradiation (60±3℃) and 4h condensation (50±3℃) alternately, according to method A in ISO 11507:2007; Type II UV lamp (UVA340nm), according to 5.1.2 of ISO 11507:2007; S2: 72h salt spray test, according to standard ISO 9227; S3: 24h low temperature exposure test (-20±2)℃.

[0064] During the UV / condensation period, it starts with UV and ends with condensation; after salt spray and before low-temperature exposure, the test panel is cleaned with deionized water but not dried; at the beginning of low-temperature exposure, the temperature reaches (-20±2)℃ within 30min.

[0065] 2. Aging indicators: corrosion at the scribe line does not exceed 3.0mm, blistering 0 (S0), rust Ri0, cracking 0 (S0), peeling 0 (S0) in the unscribe area, no adhesion damage between the first coating and the steel (unless the adhesion is ≥5MPa), each test value ≥2.5MPa.

[0066] The duration that each coating group maintained compliance with the durability standard was recorded and recorded in Table 6.

[0067] Table 6 Group Aging resistance time (h) Example 1 2688 Example 2 2676 Example 3 2680 Example 4 2685 Example 5 2690 Example 6 2679 Example 7 2484 Example 8 2589 Comparative Example 1 2037 Comparative Example 2 2154 Comparative Example 3 1718 Comparative Example 4 1983 Comparative Example 5 2006 Comparative Example 6 2108 Test Example 3: Test of heavy anti-corrosion performance 1. The adhesion of the water-based heavy-duty anti-corrosion coatings obtained in Examples 1-8 and Comparative Examples 1-6 was measured according to the cross-hatch method in GB / T 9286-1998. Each group of experiments was performed 3 times, and the average value was taken as the final result and recorded in Table 7.

[0068] 2. According to ISO12944-2017 Paints and varnishes - Anticorrosion protection of steel structures by protective coating systems - Part 6: Laboratory performance test methods, the water-based heavy anticorrosion coatings obtained in Examples 1-8 and Comparative Examples 1-6 were tested in a C5VH grade corrosion environment. The adhesion of each anticorrosion coating tested in the anticorrosion environment was then measured with reference to the pull-off method in GB / T 5210-2006. Each group of experiments was conducted 3 times, and the average value was taken as the final result and recorded in Table 7.

[0069] The definition of C5VH corrosive environment is: Exterior, industrial areas with high humidity and harsh atmosphere and coastal areas with high salinity; Buildings and areas where condensation and high levels of contamination occur and persist.

[0070] Table 7 Test Example 4 Drying Time According to the cotton ball method in GB / T 1728-1979 at room temperature, the surface drying time and actual drying time of the water-based heavy-duty anti-corrosion coatings obtained in Examples 1-8 and Comparative Examples 1-6 were respectively measured. Each group of experiments was carried out 3 times, and the average value was taken as the final result and the results were recorded in Table 8.

[0071] Table 8 in conclusion According to the performance test results in Tables 6-8, it can be seen that the water-based heavy-duty anti-corrosion coating of the present application has excellent high corrosion performance and can meet the use requirements under the C5 environment. At the same time, the water-based heavy-duty anti-corrosion coating of the present application has a faster drying speed when used.

[0072] The water-based heavy-duty anti-corrosion coating of the present application has broad application prospects in water-based metal heavy-duty anti-corrosion systems in marine environments and industrial high-corrosion environments, especially in the anti-corrosion maintenance treatment of existing equipment and facilities. The application of the water-based heavy-duty anti-corrosion coating of the present application can not only meet the requirements of heavy-duty anti-corrosion performance, but also take into account the requirements of environmental protection and low-carbon emissions, thereby providing an effective solution for the water-basedization of my country's metal heavy-duty anti-corrosion field.

[0073] According to the performance test results of Examples 1-7, Comparative Examples 1-2 and Comparative Examples 4-5, it can be seen that the composite resin system made of water-based organosilicon acrylic hybrid epoxy resin and water-based FEVE resin gives the zinc-rich primer a better adhesion to the metal surface, and can still maintain excellent adhesion and performance in a heavy corrosion environment. The coating formed by the composite resin system performs better in terms of weather resistance and adhesion.

[0074] The composite resin system combines with zinc powder to form a zinc-rich primer. A sacrificial anode protection mechanism is formed between the zinc powder and the metal substrate. On the one hand, it gives the primer a better bonding strength with the metal surface, and on the other hand, it further enhances the heavy-duty anti-corrosion performance of the coating.

[0075] The hydrophilic nano-calcium carbonate enables it to obtain a good dispersion effect in advance in the curing component, and further plays a role in filling and densifying the cured paint film, effectively improving the coating's ability to resist damage from various corrosive media.

[0076] Powdered sodium silicate is used as an alkali activator in the curing component, which effectively cuts off the channels formed by the volatilization of water after the water-based resin film is formed, significantly improves the sealing effect of the water-based resin coating, and together with zinc powder, it has a high anti-corrosion ability on the metal surface and promotes the drying speed of the coating.

[0077] According to the performance test results of Examples 1-6 and Example 8, it can be seen that the mixture of quartz sand and quartz powder can adjust the volume of the coating, thereby increasing or decreasing the thickness of the coating, and the mixture of two quartz materials with different particle sizes helps to further improve the weather resistance of the coating, thereby extending the service life of the coating.

[0078] According to the performance test results of Examples 1-6 and Comparative Examples 3-6, it can be seen that the active enhanced powder, as the main component of the mid-coat, plays a vital role in the overall anti-corrosion effect of the system. The multi-layer flaky structure formed by the composite resin system and basalt flakes forms a parallel superimposed barrier effect; the hydration products produced after alkali excitation of powdered sodium silicate and the combined filling and densification effect of nano-calcium carbonate form a barrier layer in the middle layer that can efficiently isolate the corrosive medium, effectively delaying the path and time of the corrosive medium diffusing and invading the metal surface, greatly increasing the difficulty of the corrosive medium entering the coating.

[0079] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A water-based heavy-duty anti-corrosion coating, characterized in that: The invention comprises a three-component system primer, a three-component system mid-coat and a two-component system topcoat in sequence; The raw materials of the primer include a composite resin, a curing component and a zinc-rich reinforcing powder in a mass ratio of 2:1:(2.5-3); The raw materials of the mid-coat include a composite resin, a curing component and an active reinforcing powder in a mass ratio of 1:1:(0.8-1.2); The raw materials of the topcoat include a composite resin and a curing component in a mass ratio of 2:1; The raw materials of the composite resin in the primer, midcoat and topcoat all include water-based silicone acrylate hybrid epoxy resin and water-based FEVE resin; The raw materials of the curing components in the primer, mid-coat and topcoat all include nano calcium carbonate; The raw materials of the zinc-rich enhanced powder and the active enhanced powder both include powdered sodium silicate; the active enhanced powder includes basalt flakes.

2. The water-based heavy-duty anti-corrosion coating according to claim 1, characterized in that: In parts by weight, the raw materials of the zinc-rich reinforcing powder include 15-20 parts of slag powder, 5-8 parts of powdered sodium silicate and 72-80 parts of zinc powder.

3. The water-based heavy-duty anti-corrosion coating according to claim 1, characterized in that: In terms of weight, the raw materials of the activity enhancement powder include 20-30 parts of slag powder, 1.5-2.5 parts of powdered sodium silicate, 10-20 parts of steel slag powder, 10-15 parts of basalt flakes, and 25-32.5 parts of quartz powder.

4. The water-based heavy-duty anti-corrosion coating according to claim 3, characterized in that: Also included is 10-33.5 parts of quartz sand.

5. The water-based heavy-duty anti-corrosion coating according to claim 1, characterized in that: The composite resin raw material of the primer includes 80-90 parts of water-based silicone acrylate hybrid epoxy resin and 10-20 parts of water-based FEVE resin in parts by weight; The curing components of the primer include 12-13.5 parts of curing agent, 0.1-0.4 parts of wetting agent, 0.3-0.5 parts of dispersant, 0.2-0.5 parts of defoaming agent, 0.6-1.0 parts of film-forming aid, 5-8 parts of nano calcium carbonate and 26.1-31.8 parts of water.

6. The water-based heavy-duty anti-corrosion coating according to claim 1, characterized in that: The composite resin raw material of the mid-coat includes 70-90 parts of water-based silicone acrylate hybrid epoxy resin and 10-30 parts of water-based FEVE resin in parts by weight; The curing component raw materials of the mid-coat include 10-15 parts of curing agent, 0.3-0.5 parts of wetting agent, 0.4-0.8 parts of dispersant, 0.3-0.6 parts of defoaming agent, 0.6-1.0 parts of film-forming aid, 0.3-0.6 parts of anti-settling agent, 0.3-0.6 parts of cellulose ether, 30-40 parts of nano calcium carbonate and 40.9-58.8 parts of water.

7. The water-based heavy-duty anti-corrosion coating according to claim 1, characterized in that: The composite resin raw material of the topcoat includes 60-70 parts of water-based silicone acrylate hybrid epoxy resin and 30-40 parts of water-based FEVE resin in parts by weight; The raw materials of the curing component of the primer include 9-10.5 parts of curing agent, 0.2-0.4 parts of wetting agent, 0.2-0.4 parts of dispersant, 0.2-0.5 parts of defoaming agent, 0.5-0.8 parts of film-forming aid, 0.2-0.4 parts of leveling agent, 3-6 parts of water-based color paste, 5-8 parts of nano calcium carbonate and 23.4-31.7 parts of water.

8. The water-based heavy-duty anti-corrosion coating according to any one of claims 5 to 7, characterized in that: The curing agent is a water-based non-ionic fatty amine curing agent.

9. The method for preparing a water-based heavy-duty anticorrosive coating according to any one of claims 1 to 7, characterized in that: The following steps are involved: The composite resin, curing component and zinc-rich reinforcing powder of the primer are prepared according to the raw material ratio, the three components are evenly mixed to obtain the primer, and the primer is rolled or sprayed on the metal surface, and the primer layer is obtained after drying and curing; The composite resin, curing component and active enhancement powder of the mid-coat are prepared according to the raw material ratio, the three components are evenly mixed to obtain the mid-coat, which is sprayed on the surface of the primer layer, and dried and cured to obtain the intermediate layer; The composite resin and curing component of the topcoat are prepared according to the raw material ratio, the two components are evenly mixed to obtain the topcoat, which is rolled or sprayed on the surface of the intermediate layer to form a surface layer, and is obtained after drying and curing.

Citation Information

Patent Citations

  • Petrochemical water-based high-temperature-resistant, anticorrosive and abrasion-resistant coating and method for preparing same

    CN105885620A